The Influence of Work Ethic, Work Discipline, And Physical Work Environment of Productivity Employees at PT Jenggala Keramik Bali in Jimbaran Badung Regency - I Kadek JULIARTHA; I Wayan SUPUTRA; I. B. Agung DHARMANEGARA (Journal of Governance, Taxation and Auditing, 2023)
This research was conducted at PT. Jenggala Keramik Bali is a company that operates in the production sector by analyzing HR management objects, namely work ethic, work discipline and physical work environment on employees work productivity. The sample used was 84 employees. The data analysis technique used is multiple linear regression analysis. The results of this research show that work ethic, work discipline and physical work environment influence the productivity of production employees at PT Jenggala Keramik Bali. For further research, it is hoped that the variables of job satisfaction, work stress, and work family conflict will be added to find out other factors that can influence nurse performance. It is also recommended for further research to expand the scope of research so that it can provide a broader paradigm view.